Just Membership: Between Ideals and Harsh Realities - Shachar, Ayelet (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
In this paper, Ayelet Shachar begins by restating the main idea of her important book The Birthright Lottery : Citizenship and Global Inequality (Harvard, Harvard University Press, 2009) and then goes on to address in a constructive spirit the main themes raised by the five preceding comments written by scholars in the fields of law, philosophy and political science.